A Case-Based and Evidence-Based Seminar Series for Senior Dental Students - Fred Fendler; Terry E. Hoover; Lucinda J. Lyon (Association of American Medical Colleges, 2012)
Abstract Introduction The teaching module is a small portion of a multidisciplinary seminar series which uses an evidence- and case-based approach to teach senior-year dental students about the parallels seen in treatment decision-making within clinical dentistry. Methods This senior-year seminar focuses on two dental themes: (1) trauma and rehabilitation of the young permanent dentition, and (2) infections and the acute odontogenic emergency. A senior faculty member directs a case-based seminar with group discussion focusing on assigned literature readings and associated cases. Two to three additional interdisciplinary faculty from contributing departments participate in each seminar theme. The seminar format includes directed questioning of all students present about the relationship between the theme, the literature readings, and cases presented by the students. The two faculty PowerPoints included in this teaching module are used to stimulate conversation. Questions are asked randomly throughout the seminar. The seminar portion of class is followed by a presentation session during which four students discuss a case from their personal clinical patient pool. Faculty and students alike engage the presenting student on aspects of the clinical case presented. Students are assessed in their seminar series via their participation in the case-based discussions, faculty evaluation of student presentation, use of literature to support treatment decisions, and case-based written examinations containing both multiple-choice and short-essay questions. Results This course has been implemented for 5 years. We believe that based on the results of our examinations and other assessment tools, the course has been very effective in reaching our stated educational objectives. Discussion Future iterations of the course will likely have different themes as the field evolves, but this format is easily adaptable to effectively teach different themes.